2011
DOI: 10.1111/j.1753-0407.2011.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the effects of the traditional Chinese medicine Rehmannia Six Formula on diabetes mellitus and its complications

Abstract: Rehmannia Six Formula (RF) is a formula that is commonly used in Traditional Chinese Medicine to treat patients with diabetes. A literature search was performed in PubMed for the years 2000–2009 using the key words RF, Rehmannia glutinosa, Fructus Corni, Dioscorea sp. (D. alata, D. opposita, D. batatas), Poria cocos, Alisma sp. (A. orientalis, A. plantago aquatica), and Paeonia suffruticosa/Cortex Moutan. On the basis of the publications found, RF appears to have beneficial effects on blood glucose, neuropathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 43 publications
0
33
2
Order By: Relevance
“…There is accumulating evidence that herbal extracts have been found attractive in controlling diabetes with little toxicity. [7][8][9] This present study was therefore performed to validate our hypothesis for the anti-diabetic potential of EOPK, based on our previous report on the anti-hyperlipidemic effect 16) of EOPK, since the metabolic syndrome includes obesity, diabetes and hyperlipidemia. There are the two species of Pinus calorpreferens and Pinus glomerata from Pinus koraiensis in Korea, 19) and Yang et al have identified the presence of the eight compounds, 8(14)-podocarpen-13-on-18-oic acid, 15-hydroxydehydroabietic acid, 12-hydroxyabietic acid, lambertianic acid, dehydroabietic acid, sandaracopimaric acid, -sitosterol and daucosterol.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is accumulating evidence that herbal extracts have been found attractive in controlling diabetes with little toxicity. [7][8][9] This present study was therefore performed to validate our hypothesis for the anti-diabetic potential of EOPK, based on our previous report on the anti-hyperlipidemic effect 16) of EOPK, since the metabolic syndrome includes obesity, diabetes and hyperlipidemia. There are the two species of Pinus calorpreferens and Pinus glomerata from Pinus koraiensis in Korea, 19) and Yang et al have identified the presence of the eight compounds, 8(14)-podocarpen-13-on-18-oic acid, 15-hydroxydehydroabietic acid, 12-hydroxyabietic acid, lambertianic acid, dehydroabietic acid, sandaracopimaric acid, -sitosterol and daucosterol.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6] Recent hypoglycemic herbal medicines are therefore considered attractive, since they are suitable for long-term diabetes control with little toxicity. 7,8) The chloroform fraction of Andrographis paniculata has recently exerted an anti-diabetic effect on diabetic albino mice, 9) a cinnamon extract has shown a moderate effect in reducing the fasting plasma glucose concentration in diabetic patients with poor glycaemic control, 10,11) and a curcumin extract has improved the overall function of -cells from T2DM patients with very minor adverse effects. [12][13][14][15] The metabolic syndrome includes obesity, hyperlipidemia and diabetes, and we can hypothesize on the anti-diabetic potential of EOPK, given that our previous study has shown the essential oil from leaves of Pinus koraiensis (EOPK) to exert its antihyperlipidemic effects by upregulating the low-density lipoprotein receptor and inhibiting cholesterol acyltransferases.…”
mentioning
confidence: 99%
“…Similar to another study in Taiwan, 3 Liu-Wei-Di-Huang-Wan and its derivatives were found to be the most common herbal formulae prescribed by TCM doctors for the treatment of diabetes in Taiwan. Recent scientific evidence has suggested that Liu-Wei-Di-Huang-Wan reduced blood glucose, relieved neuropathy and nephropathy in diabetes, 24 and improved the lipid profile to reduce cardiovascular risk. 25 Animal studies revealed that Ba-Wei-Di-Huang-Wan increased insulin synthesis and release, 26,27 suppressed the release of glucose from the liver, 26 normalized or suppressed the small intestinal disaccharidase activity, 28 reduced the damage caused by oxidative stress, 29,30 and prevented diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the ginkgo leaf extract also played a part in the inhibition of platelet aggregation, antioxidation, dilation of blood vessel, and improving the abnormal blood rheology [2326]. These pharmacological characteristics might be beneficial to the prevention of diabetic vascular complications [27, 28]. (2) The two drugs belonged to Chinese patent medicines with the advantages of stable composition, convenient storage and taking, and good adherence which ensured higher scientificity and repeatability to the study results.…”
Section: Discussionmentioning
confidence: 99%